Features of military reform in the process of administrative and political construction in the Circassian aul societies of the Kuban region (the case of the aul of Khakurinokhabl, 1887) - Ruslan Sultanovich Kandor (Вестник Майкопского государственного технологического университета, 2023)
The article discusses the events that took place in July 1887 in the Circassian aul of Khakurinokhabl during the implementation of the military reform in the Circassian aul societies of the Kuban region, which revealed the existence of a socio-political confrontation within the aul society. Great importance is attached to the study of specific events that took place in the Circassian aul societies of the Kuban region during the preparation of reforms that contribute to the complex process of strengthening the Russian influence and maintaining civil order in the Circassian aul societies.The author uses a wide range of sources on the history of the Adyghs (Circassians), which include archival materials, suggesting a comprehensive coverage of historical facts on this issue.The method of accumulation of factual material with subsequent analysis and obtaining the next, higher degree of generalization has been used. The principle of historicism plays an important role in the study of the problem, which has made it possible to consider the civil disturbances in the aul of Khakurinokhabl in dynamics from actual events in specific historical conditions in close connection with the administrative and socio-economic policy of the authorities to theoretical discussions about their causes and consequences.The article consistently describes the events that took place during the riots in the aul of Khakurinokhabl, which has made it possible to identify the role of individual characters and claimsagainst the aul authorities put forward by part of the aul society. The author reveals the activities of the head of the Maikop district of the Kuban region to maintain order in the aul of Khakurinokhabl.The author comes to the conclusion that in the course of the military reform in the Circassian aul communities of the Maikop district of the Kuban region, the Russian officials did not fully take into account the already existing historical experience of reforms among the Circassian population. Ignoring the interests of the most disadvantaged part of society by the old aul elites, pushed Circassian women, as guardians of the hearth and well-being of their families, to take active actions of protest together with men.